Across six societies children engage in costly third-party punishment of unfair sharing - Katherine McAuliffe; Samantha Bangayan; Tara Callaghan; John Corbit; Henry G. W. Dixson; Yarrow Dunham; Ann Finkel; Emily Otali; Sophie Riddick; Patrick Tusiime; Felix Warneken (Communications Psychology)
Abstract Third-party punishment of unfairness shows striking cross-societal variation in adults, yet we know little about where and when in development this variation starts to emerge. When do children across societies begin to pay a cost to prevent unfair sharing? We present an experimental study of third-party punishment of unfair sharing across N = 535 children aged 5–15 from communities in six diverse countries: Canada, India, Peru, Uganda, USA, and Vanuatu. We tested whether children were more likely to punish equal or selfish (maximally unequal) distributions between two absent peers. We also tested whether decisions depended on whether such punishment was costly—participants had to sacrifice their own rewards to punish—or free. Our study generated three main findings. First, children across societies engaged in third-party punishment of selfishness: they were more likely to punish selfish than equal distributions. Second, older children were more likely than younger children to punish selfish sharing in Canada, India, Peru, and the USA. Third, children in Canada and the USA punished more in general in the Free condition than in the Costly condition, whereas children in Uganda punished selfishness more in the Costly condition. These findings show that children from six diverse societal contexts consistently took a stance against unfair sharing, in some cases even sacrificing their own rewards to intervene against selfishness in their peers. We highlight and discuss similarities and differences in cross-societal patterns of age-related differences in third-party punishment and suggest potential explanations for these patterns.